2022
DOI: 10.1002/slct.202201135
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrogenative Esterification and Dehydrative Etherification by Coupling of Primary Alcohols Based on Catalytic Function Switching of an Iridium Complex

Abstract: Esters and ethers are widely used in modern organic synthesis. In recent years, the synthesis of esters by the dehydrogenative coupling of primary alcohols has been reported to be an environmentally benign process. In this situations, if a single catalyst can be used for the synthesis of either esters or ethers by making slight alterations to the reaction conditions, the value of the synthetic methodology would increase. In this study, we successfully developed a new catalytic function switching system: not on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…The 1 H NMR spectrum of 5A is consistent with the asymmetric substitution of the NDI moiety, as evidenced by the appearance of an AB system centered at 8.77 ppm assigned to two pairs of unequivalent protons of the naphthalene core of the NDI unit. As for complexes 2A and 2B, in 5A, the ligand is coordinated to the Ir(III) center via a (C NHC ,C pyr )-chelating form, as evidenced by the two doublets observed at 8.25 and 6.95 ppm assigned to the protons of the pyridine ring, and to the resonances at 164.6 and 163.8 ppm that appear on the 13 C NMR spectrum, assigned to the Ir−C carbene 13 and Ir−C (pyridine) carbons, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 1 H NMR spectrum of 5A is consistent with the asymmetric substitution of the NDI moiety, as evidenced by the appearance of an AB system centered at 8.77 ppm assigned to two pairs of unequivalent protons of the naphthalene core of the NDI unit. As for complexes 2A and 2B, in 5A, the ligand is coordinated to the Ir(III) center via a (C NHC ,C pyr )-chelating form, as evidenced by the two doublets observed at 8.25 and 6.95 ppm assigned to the protons of the pyridine ring, and to the resonances at 164.6 and 163.8 ppm that appear on the 13 C NMR spectrum, assigned to the Ir−C carbene 13 and Ir−C (pyridine) carbons, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…17 Albrecht and co-workers observed the homocoupling etherification of benzyl alcohol using a Ir(III)Cp* complex with a chelating pyridine-NHC ligand, but the reaction was not selective (benzaldehyde was also produced), and the reaction conditions used were harsher than those used by us (150 °C, catalyst loading 2 mol %). 10d In a more recently published work, Fujita and co-workers described the homocoupling of a series of primary alcohols at a lower temperature (120 °C) using a series of Cp*Ir(III) complexes, but the reaction required a hydrogen atmosphere and a catalyst loading of 1 mol %, 13 and the product yields were slightly below 90%. As for the activity of [IrCp*Cl 2 ] 2 , in our previous studies, we showed that it was able to produce the cross-coupling etherification of benzyl alcohol and n-butanol under the exact same reaction depicted in Table 1, affording 90% of the cross-coupling product, although a 2 mol % of catalyst loading (based on the amount of metal) was required.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation